ENTREPRENEURIAL DREAMS AND SUCCESSION PLANNING IN INDONESIAN SMALL FAMILY BUSINESSES: CULTURAL INSIGHTS FROM MARTABAK SELLERS - Widagdo, Agus Suryo; Soehadi, Agus W. (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
Family businesses play a vital role in Indonesia’s economy, yet many small family-owned enterprises struggle with succession due to informal structures, generational reluctance, and changing career preferences. This study explores how succession planning is shaped by entrepreneurial dreams and cultural values in the Martabak (Indonesian pancake) industry. Using a qualitative case study approach based on semi-structured interviews with incumbent business owners, the research addresses a key gap: prior studies emphasize formal governance in medium and large enterprises, while little is known about informal, aspiration-driven succession in small family firms. By applying succession planning models within the Indonesian cultural context, this study contributes novelty by framing succession through the lens of incumbents’ “entrepreneurial dreams,” highlighting the interplay between aspirations, Hofstede’s cultural dimensions, and successor development. Findings reveal that while formal succession plans are rare, incumbents encourage successors to pursue higher education and external work experience before returning to the family business. Succession activities remain relational, relying on trust, exposure, and experiential learning. The study concludes that entrepreneurial dreams, embedded in collectivism and family loyalty, are central to sustaining continuity. Practical recommendations include early successor involvement, structured mentorship, and culturally aligned entrepreneurship programs to support small enterprises in balancing tradition with modernization.